Dampak Sosial-Ekonomi Pembangunan Sindu Kusuma Edupark di Kabupaten Sleman - Auliana Rahmasari; Samodra Wibawa; Rizki Rahmasari (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
This study aimed to determine the socio-economic impacts of the development of tourist destination Sindu Kusuma Edupark (SKE) on local community. Six indicator were examined: employment opportunity, employment absorption, income, welfare, general infrastructure, and government revenue. Survey data from three sub-villages (dusun) were included in the analysis. The findings of this study demonstrated that the development of SKE has various impact to the local community. Dusun Kragilan, the closest sub-village to the tourist destination, has received positive economic impact because most of its residents have a small business at SKE. However, SKE has also negative impact as tourist crowds often caused congestion in the area, making it less conducive to local people to do their daily activities. For people in Dusun Ngaglik and Dusun Rogoyudan, which are located farther away from the tourist site, SKE has not seemed to provide a meaningful economic benefit. Despite the fact that they receive contributions in cash from SKE, there is only limited opportunity for participation in the development of SKE. From this study is recommended to provide persuasive approach to the community in three nearby sub-villages in order to establish SKE as a tourist site that provides positive socio-economic impact for local community.